2016
DOI: 10.1021/jacs.6b11067
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Interfacial Proton-Coupled Electron Transfer Mechanism in the Photocatalytic Oxidation of Methanol to Formaldehyde on TiO2(110)

Abstract: CHOH on a single-crystal rutile TiO(110) surface is a widely studied model system for heterogeneous photocatalysis. Using spin-polarized density functional theory with a hybrid functional (HSE06), we study the photocatalytic oxidation of CHOH adsorbed at a coordinately unsaturated Ti site as an excited-state process with triplet spin multiplicity. The oxidation to CHO is stepwise and involves a CHO intermediate. The first O-H dissociation step follows an excitonic interfacial proton-coupled electron transfer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 77 publications
3
94
1
1
Order By: Relevance
“…The smaller semicircle in the EIS Nyquist plot suggests a fast interfacial charge transfer in the semiconductor. 58,59 This result also demonstrates that the 1D Ag@CdS hierarchical nanowires display superior efficiency compared to that of the CdS nanoflower in separating the electron-hole pairs, which is consistent with the results of PL spectroscopy.…”
Section: Inorganic Chemistry Frontiers Research Articlesupporting
confidence: 87%
“…The smaller semicircle in the EIS Nyquist plot suggests a fast interfacial charge transfer in the semiconductor. 58,59 This result also demonstrates that the 1D Ag@CdS hierarchical nanowires display superior efficiency compared to that of the CdS nanoflower in separating the electron-hole pairs, which is consistent with the results of PL spectroscopy.…”
Section: Inorganic Chemistry Frontiers Research Articlesupporting
confidence: 87%
“…As a matter of fact, in the EIS Nyquist plot, the smaller semicircle size indicates fast interfacial charge transfer in the semiconductor. 47,48 The above result suggests that more effective interfacial charge transfer occurs on the twinned anatase TiO 2 photocatalyst rather than anatase and brookite TiO 2 under these conditions. Based on these results, it was concluded that the enhancement of the photocatalytic hydrogen evolution activity of the twinned anatase TiO 2 nanocrystals was attributed to the faster separation of photogenerated carriers and lower recombination of photoinduced electron-hole pairs.…”
Section: Resultsmentioning
confidence: 82%
“…For example, the mechanisms of CH 3 OH photolysis on R‐TiO 2 (110) proposed by Henderson's group and Wang's group mainly consider the role of holes. However, Migani and Blancafort predicted that the photooxidation of CH 3 OH on R‐TiO 2 (110) is initiated by interfacial excitons rather than separated holes using DFT calculations. The O–H dissociation step occurs through an excitonic interfacial PCET mechanism with hole transferring to the CH 3 O Ti groups, forming excited‐state CH 3 O Ti • intermediates ( Figure ).…”
Section: Reaction Mechanisms In Tio2 Photocatalysismentioning
confidence: 99%